RhoGTPase stimulation is associated with strontium chloride treatment to counter simulated microgravity-induced changes in multipotent cell commitment - Fiona Louis (Nature Portfolio, 2017)
Countering Bone Loss in Space A chemical element naturally found for instance in seafood or grains, could counter bone loss from long-term spaceflight. Alain Guignandon and colleagues from the Université de Lyon à St-Etienne in France exposed multipotent embryonic fibroblasts to microgravity conditions similar to those found in space. They found the balance shifted in these stem cells from differentiating to bone-forming cells (osteoblasts) to differentiating to fatty-tissue forming cells (adipocytes). When the cells were treated with strontium, the shift toward osteoblastogenesis was regained. Strontium achieves this by sustaining the activity of two proteins that play a role in bone development but are suppressed in space. Strontium’s effect on the proteins could happen via release of vascular endothelial growth factor, which, under normal gravity conditions, plays a role in committing the cell to differentiation into osteoblasts rather than adipoyctes.